Competitiveness, migration, and mobility in the global city: Insights from Sydney, Australia - Richard Hu (Economies, 2015)
The global city thesis and the migration thesis concern two important dimensions of the impacts of contemporary globalization on cities. The two theses are intrinsically linked. The central question is how we should approach migration in the new context of the global city, and how we should articulate their interrelationships. To address this question, we construct an integrative analytical framework linking global city and migration, and empirically apply it to Sydney. We build a set of indexes to measure global competitiveness, global migration, and global mobility of communities across global Sydney. The findings reveal that global competitiveness-the defining capacity of Sydney as a global city-has very weak association with global migration that measures the stock of foreign born population, but has very strong association with global mobility that measures the people movement in recent years. These findings call for a redefinition of migration to incorporate people movement to better capture the interplay between global city and migration.
Keywords: R11; R12; 330; global city; competitiveness; migration; mobility; Sydney